2015
DOI: 10.1007/s00198-015-3168-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors is associated with fractures in young adults: a population-based study

Abstract: Purpose Proton pump inhibitors (PPIs) are associated with fracture in adults with osteoporosis. Because PPI therapy may interfere with bone accrual and attainment of peak bone mineral density, we studied the association between use of PPIs and fracture in children and young adults. Methods We conducted a population-based, case-control study nested within records from general medical practices from 1994 to 2013. Participants were 4–29 years old with ≥1 year of follow-up who lacked chronic conditions associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 38 publications
3
76
1
3
Order By: Relevance
“…Sharara et al demonstrated in 2012 that PPIs do not have any harmful impact on children's and young adults’ level of parathyroid hormone in serum for two groups of 29 participants after 12 weeks of PPI intake. On an other hand, a recent high‐quality observational study reported a higher risk of fractures among young adults receiving PPI …”
Section: Introductionmentioning
confidence: 97%
“…Sharara et al demonstrated in 2012 that PPIs do not have any harmful impact on children's and young adults’ level of parathyroid hormone in serum for two groups of 29 participants after 12 weeks of PPI intake. On an other hand, a recent high‐quality observational study reported a higher risk of fractures among young adults receiving PPI …”
Section: Introductionmentioning
confidence: 97%
“…ASD is also associated with recurring gastrointestinal diseases such as colitis and malabsorption which affect mineral nutrition [2226]. Finally, children with ASD are often chronically exposed to anti-epileptic [27] and antipsychotic medications [28], selective serotonin reuptake inhibitors(SSRIs) [29], and proton pump inhibitors [30, 31], all of which can have deleterious effects on bone.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors include genetics (Estrada et al 2012), gender (Nishiyama et al 2012), race and ethnicity (Warden et al 2006), mechanical loading of bone (Deere et al 2012; Ginty et al 2005), calcium and vitamin D intake (Lehtonen-Veromaa et al 2002), nutritional status (Davies et al 2005), presence of concomitant chronic illnesses, and life style choices such as smoking and alcohol intake (Riggs and Melton 1986). Risk factors for low BMD in ASD include reduced mechanical loading of bone from decreased physical activity (Pan 2008), impaired calcium and vitamin D intake, particularly in those with food aversions and restricted diets (Hyman et al 2012), higher rates of co-morbid neurologic, psychiatric and gastrointestinal illnesses, and use of medications that impact bone, such as antiepileptics that impair vitamin D metabolism (Sheth et al 2008; Chou et al 2007), antipsychotics (Calarge et al 2015; Roke et al 2012) and proton pump inhibitors (Freedberg et al 2015). …”
Section: Introductionmentioning
confidence: 99%